2019
DOI: 10.1002/cnm.3254
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a coupled fluid‐structure interaction model of the left atrium and mitral valve

Abstract: We present a coupled left atrium‐mitral valve model based on computed tomography scans with fibre‐reinforced hyperelastic materials. Fluid‐structure interaction is realised by using an immersed boundary‐finite element framework. Effects of pathological conditions, eg, mitral valve regurgitation and atrial fibrillation, and geometric and structural variations, namely, uniform vs non‐uniform atrial wall thickness and rule‐based vs atlas‐based fibre architectures, on the system are investigated. We show that in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 81 publications
(158 reference statements)
0
34
0
Order By: Relevance
“…Several CFD studies have explored the effect of LAA geometry on blood flow but, taken together, have offered ambiguous results. Bosi et al (2018) found that LAA morphologies that are clinically associated with higher stroke incidence have impaired blood washout, whereas other studies (Garcia-Isla et al, 2018;Feng et al, 2019;Masci et al, 2019) reported that LAA stasis depends critically on additional factors such as PV inflow patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Several CFD studies have explored the effect of LAA geometry on blood flow but, taken together, have offered ambiguous results. Bosi et al (2018) found that LAA morphologies that are clinically associated with higher stroke incidence have impaired blood washout, whereas other studies (Garcia-Isla et al, 2018;Feng et al, 2019;Masci et al, 2019) reported that LAA stasis depends critically on additional factors such as PV inflow patterns.…”
Section: Introductionmentioning
confidence: 99%
“…IFE further avoids the use of body‐conforming discretizations between the fluid and structure, 17 and hence overcomes mesh distortion issues in body‐fitted approaches 18,19 . One such an example is shown in simulations of FSI in the vicinity of the cardiac valves 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…18,19 One such an example is shown in simulations of FSI in the vicinity of the cardiac valves. 20,21 The extension of IFE formulations to treat poroelastic structures is relatively recent. 22,23 Strychalski et al 22 developed a poroelastic IB method for cellular mechanics, using a Lagrangian reference frame while the fluid moving both in and outside of the cell is described in Eulerian form although this approach only considers the dilute limit.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, two main standpoints are currently adopted: Fluid-Structure Interaction (FSI) simulations and prescribed-motion Computational Fluid Dynamics (CFD). The first approach, employed for example in [6], [7], [8], [9], [10], [11], consists in the coupled solution of the fluid dynamics of blood flow and of the structure mechanics of the myocardium and valves, thus entailing a possibly very high computational cost. On the other hand, in image-based CFD, the displacement of the myocardium and valves leaflets is reconstructed from kinetic medical images and then prescribed as endocardial data to obtain the fluid domain configuration.…”
Section: Introductionmentioning
confidence: 99%